Detection and amplification of putative [NiFe] hydrogenase operon in anoxybacillus sp. SK3-4 [electronic resource] - Mohd. Adhha Hussin, 1977-; Mohd. Firdaus Abdul Wahab, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (2014)
Thesis (Sarjana Sains (Bioteknologi)) - Universiti Teknologi Malaysia, 2014